Ultra-Low Reflective Silicon Surfaces for Photovoltaic Applications. (2016) - Lim, J.W.M.; Huang, S.Y.; Chan, C.S.; Xu, S.; Wei, D.Y.; Guo, Y.N.; Xu, L.; Ostrikov, K.
Abstract: Silicon based photovoltaic cells still remain a mainstay in the industries due to its relatively low cost for manufacturing and implementation. A good knowledge base of the material has also been built up over the years and there is no doubt that silicon based photovoltaic cells would continue to lay the basis for renewable energy for many years to come. However, it is widely known that conventional silicon photovoltaic cells have relatively lower power conversion efficiencies as compared to its next generation counterparts. This is partly due to the high optical losses on surfaces, resulting in poor harvesting of energy from incident light. In this work, an ICP process was developed to fabricate ultra-low reflective silicon surfaces for photovoltaic applications. An Ar + H2 feedstock was used to texture nanocones on the surface of silicon wafers, reducing the reflective losses and forming a high quality pn junction simultaneously. Reflectivity of the samples were characterised with a Zolix SCS10-X150-DSSC UV-Vis spectrometer with an attached integrating sphere, while the photovoltaic properties were measured with a PV characterization suite from Sinton instruments. The low reflectivity with promising electronic properties of the processed materials shows propitious potential for applications in the field of photovoltaics.